Membaca Ulang Maskulinitas: AU Boys Love Sebagai Ruang Dekonstruksi Maskulinitas dalam Budaya Populer - Ade Fristy Syahara; Andi Hikmawati Yunus; Rosmita (CV. Dalle’ Deceng Abeeayla, 2026)
This study aims to analyze the role of AU Boys Love as a medium capable of providing information and knowledge in shaping new perspectives on masculinity. Data were collected through a cyber ethnography approach, utilizing observation methods and in-depth interviews. The cyber ethnography approach was chosen because it is considered appropriate for gaining an understanding of virtual communities, and is deemed capable of providing accurate data about such communities. The data in this study were then analyzed using the deconstruction theory of Jacques Derrida. The findings indicate that the internalization of knowledge related to soft masculinity occurs through narratives contained in AU Boys Love stories, as well as through interactions with fellow AU Boys Love fans encountered in virtual spaces. Through this internalization process, a shift in meaning occurs with regard to hegemonic masculinity. This study demonstrates that virtual spaces and Boys Love narratives provide readers with opportunities to develop a more inclusive understanding of masculinity, challenging established hegemonic masculine norms and opening space for more diverse forms of self-expression